(untitled) (Indonesia Media Law Review, 2025)
The rapid growth of the digital economy in Indonesia has drastically changed the nature of online commerce and prompted urgent considerations regarding the legal responsibilities of digital commerce platforms, especially user-generated content that violates public ethics. This article aims to analyze and compare the preventive, corrective, and compensatory obligations of digital platforms in Indonesia, the European Union, and the United States. This study uses normative legal research with comparative studies, reviewing the Electronic Information and Transaction Law (ITE) in Indonesia, the Digital Services Act of the European Union (EU), and Section 230 of the Communications Decency Act of the United States. The results show that Indonesia implements a knowledge-based and conditional liability system, which requires platforms to remove illegal content after receiving notification, but does not introduce an absolute liability system. The EU adopts a risk-based and proportional approach that reflects differences in the scale and impact of platforms, and focuses on systemic risk management and transparency. On the other hand, the US model tends to prioritize platform autonomy by providing broad immunity. The findings show that although Indonesian regulations are in line with innovation and consumer protection, they are still not strict enough in terms of systemic risks in algorithms and cultural commodification. This study emphasizes that adopting explicit risk assessment standards, enhanced transparency requirements, and stronger user compensation systems presents an opportunity for Indonesia, drawing on the experiences of the EU and the US, to achieve greater platform accountability and sustainable digital growth.